Stability and Surface Topography Evolution in Nanoimprinted Polymer Patterns under a Thermal Gradient - Ding, Yifu; Qi, H. Jerry; Alvine, Kyle J; Ro, Hyun Wook; Ahn, Dae Up; Lin-Gibson, Sheng; Douglas, Jack F; Soles, Christopher L (Macromolecules, 2010)
Nanostructures created in polymer films by nanoimprint lithography are subject to large stresses, both those from the imprinting processes as well as stresses arising from the intrinsic thermodynamic instabilities. These stresses can induce nanostructure deformations that compromise the intended function of the imprinted pattern. Controlling these stresses, and thus the stability of the imprinted patterns, is a key scientific issue for this technology. The requirement of film stability against dewetting requires the use of entangled polymer films, which necessitates an understanding of complex viscoelastic response of these materials to large stresses. Here we investigate the evolution of the surface topography of nanoimprinted patterns in polystyrene films through a high throughput annealing approach in which the patterns are annealed for a fixed time on a controlled temperature gradient. Using principles of time−temperature superposition we systematically explore the effect of varying basic system variables such as pattern feature size, polymer molecular mass, imprinting temperature, on nanopattern stability, and on the evolution of imprinted patterns driven by surface tension and internal stress. Nanostructure collapse generally occurs through a combination of a “slumping” instability, where the imprinted film simply relaxes toward a planar film and the pattern height decreases with time, and a lateral “zigzag” instability in the nanoimprinted lines.